Prevalence of COVID-19 associated xerostomia, taste and smell disturbances over 3 years in an Egyptian sample: a cross-sectional study - Dalia Ghalwash; Ahmed Hamdy; Asmaa Abou-Bakr (Exploration of Medicine, 2025)
Aim: Although xerostomia, smell, and taste dysfunctions are prominent signs of COVID-19 infection, long-term data regarding their prevalence and recovery rates is scarce. Accordingly, this study aimed to evaluate the frequency and persistence of xerostomia, taste, and smell disturbances in COVID-19 survivors over 3 years in an Egyptian sample. Methods: This cross-sectional study used an online questionnaire to assess the oral symptoms of xerostomia, which include altered taste and smell. Data was collected from 826 patients recovered from COVID-19. Results: Xerostomia was the most frequent finding affecting 73.6% of the studied sample, followed by smell disturbances affecting 67.8%, and altered taste reported by 54.6%. Xerostomia lasted less than 1 year in 48.3% of cases, up to 2 years in 10.4%, and up to 3 years in 7.2% of the study sample. Altered taste lasted less than 1 year in 77.8% of cases, up to 2 years in 2%, and up to 3 years in 0.4% of the study sample. Smell disturbances lasted around 1 month in 62.1% of cases, from 2–3 months in 36.1%, up to 1 year in 1.6%, and up to 2 years in 0.2% of the study sample. Xerostomia altered taste and smell, which impaired the quality of life and was more frequently observed in females than in males in the studied sample. Conclusions: COVID-19 has a major and long-term impact on oral health, with frequent, intense, and longstanding oral symptoms that may impair a patient’s quality of life.